1881 Wash. Code 181, Criminal Procedure, Offenses Against Public Policy, ch. 73, § 929 - (:unkn) unknown (General Publisher, 1881)
Prohibited the carrying of “any concealed weapon.” Punishable by fine up to $100 or imprisonment up to 30 days.
--
Keywords: CARRY - CONCEALED